Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Kinerja Usaha Mikro di Kota Batam - Martin, Frendy; Neni Marlina Br. Purba (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the impact of financial literacy and financial inclusion on the performance of Micro Enterprises in the city of Batam. The method employed in this research is quantitative, utilizing primary data collection through questionnaires. The data collection process was carried out via Google Forms and in-person interactions. The research sample consists of 250 Micro Enterprises registered with the Department of Cooperatives and Micro Enterprises in Batam City, selected through simple random sampling technique. Data analysis was conducted using descriptive analysis and quantitative analysis methods, including data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The analysis process utilized the SPSS software version 25. Research findings indicate that financial literacy has a positive and significant impact on the performance of Micro Enterprises in Batam City. Additionally, financial inclusion also exhibits a positive and significant impact on the performance of Micro Enterprises in Batam City. The results of this research contribute significantly to the understanding of the interrelation between financial literacy, financial inclusion, and the performance of Micro Enterprises. The implications of these findings can serve as a foundation for the development of policies supporting the enhancement of literacy and financial inclusion at the microeconomic level in Batam City.